A revision of the species of the pseudoscorpion subgenus Chthonius (Ephippiochthonius) (Arachnida, Pseudoscorpiones, Chthoniidae) from Italy and neighbouring areas - Gardini, Giulio (Zootaxa, 2013)
A taxonomic revision and a key to the species of the subgenus Chthonius (Ephippiochthonius) Beier, 1930 from Italy, Cor-sica and the Swiss Canton of Ticino are provided. The species are arranged in two species-groups (tetrachelatus group and fuscimanus group) on the basis of the shape of pedipalpal hand and of the type of dentition of the fixed and movable chelal fingers. The following new species are described: i) in the tetrachelatus group: Chthonius (E.) altamurae n. sp. (♀, loc. typ.: Apulia, Bari Prov., Altamura, Grotta Lamalunga 1295 Pu/BA), C. (E.) elymus n. sp. (♂, loc. typ.: Sicily, Trapani Prov., Custonaci, Abisso del Purgatorio 8064 Si/TP), Chthonius (E.) messapicus n. sp. (♂, loc. typ.: Apulia, Brindisi Prov., San Pietro Vernotico, Cerano); ii) in the fuscimanus group: C. (E.) aeneae n. sp. (♂♀, loc. typ.: Liguria, Genoa Prov., Sestri Levante, Punta Manara), C. (E.) etruscus n. sp. (♂♀, loc. typ.: Tuscany, Grosseto Prov., Semproniano, Grotta di Montecchio 254 To/GR), C. (E.) gallii n. sp. (♂♀, loc. typ.: Liguria, Savona Prov., Bergeggi), C. (E.) intemelius n. sp. (♂♀, loc. typ.: Liguria, Imperia Prov., Apricale, Mt Cianela), C. (E.) latellai n. sp. (♂♀, loc. typ.: Latium, Latina Prov., Bassiano, Grotta di Fiume Coperto 1361 La/LT), C. (E.) ligur n. sp. (♂♀, loc. typ.: Liguria, Imperia Prov., near Baiardo), C. (E.) magrinii n. sp. (♂, loc. typ.: Latium, Frosinone Prov., San Giovanni Incarico, Grotta sulla strada per il Santuario della Madonna della Guardia n. c. La/FR), C. (E.) monguzzii n. sp. (♂♀, loc. typ.: Lombardia, Brescia Prov., Sulzano, Oricina de la Pofa del Giardì 438 Lo/BS), C. (E.) sulphureus n. sp. (♂♀, loc. typ.: Marche, Ancona Prov., Genga, Grotta di Frasassi 1 Ma/AN), C. (E.) tyrrhenicus n. sp. (♂♀, loc. typ.: Liguria, Genoa Prov., Genoa, Quinto al Mare, Mt Moro). The following new synonymies are proposed: Chthonius (E.) bauneensis Callaini, 1983 is a junior subjective synonym of C. (E.) berninii Callaini, 1983 (n. syn.), C. (E.) aegatensis Callaini, 1989 is a junior subjective synonym of C. (E.) berninii Callaini, 1983 (n. syn.), Chthonius (E.) maltensis Mahnert, 1975 is a junior subjective synonym of Chthonius (E.) concii Beier, 1953 (n. syn.), Chthonius (E.) bartolii Gardini, 1976 is a junior subjective synonym of Chthonius (E.) concii Beier, 1953 (n. syn.), Chthonius (E.) elbanus Beier, 1963 is a junior subjective synonym of Chthonius (E.) nanus Beier, 1953 (n. syn.), Chthonius (E.) cavicola Gardini, 1990 is a junior subjective synonym of Chthonius (E.) troglophilus Beier, 1930 (n. syn.). Thirty-nine species of Ephippiochthonius are known at present from the above-mentioned areas, of which one is presumably endemic to Sicily, four to Sardinia and four to Corsica. C. (E.) gibbus Beier, 1953 is excluded from the Ital-ian fauna and C. (E.) vachoni Heurtault-Rossi, 1963 is newly recorded from Italy. Chthonius (E.) poeninus Mahnert, 1979 is transferred to the subgenus Globochthonius Beier, 1931.